Rabindra complex :Dakshindihi, Phultola, Khulna - Raham, Chowdhury Tasneem (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.